Biology of selective caries removal: a systematic scoping review protocol - Helge Knüttel; Matthias Widbiller; Rita Weiler; Kerstin M Galler; Wolfgang Buchalla; Konstantin J Scholz (BMJ Open)
Introduction Primary goal of restorative caries therapy is to preserve pulp vitality and the dentition. Whereas the conventional approach of complete caries removal aims at the elimination of all affected substances without regard to losses of hard tissue or pulp vitality, the innovative concept of selective caries removal (SCR) is characterised by a targeted and non-invasive excavation. It presents a lower risk of accidental pulp exposure, which reportedly has a positive effect on tooth survival. Although clinical data show the benefits of SCR, knowledge about the biological processes during this procedure in the pulp-dentine complex of permanent teeth is scarce. Hence, the aim of this work is to systematically scope the existing literature and map the existing evidence according to the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews guideline. This protocol details the scoping review’s methodological and analytical approaches.Methods and analysis First, a structure was established (phase I) as basis for a systematic scoping of literature (phase II). In the course of phase I, a total of 100 systematic reviews related to selective caries removal were searched in MEDLINE and information or theories on the biological processes were extracted. During the entire procedure, two reviewers independently screened the articles, and controversies were mediated by vote of a third reviewer. Eventually, it became apparent that different biological explanations can be organised into four categories: pulp response, cavity seal, remaining bacteria and cavity liner. Based on this structure, a search for original publications (phase II) will be performed and retrieved evidence will be assembled using a predefined conceptual framework.Ethics and dissemination As primary data will not be included in this study, ethical approval is not required. Findings will be disseminated through peer-reviewed publications, conference presentations and summaries for key stakeholders.